2012
DOI: 10.3109/19396368.2012.692431
|View full text |Cite
|
Sign up to set email alerts
|

Significant improvement of sperm DNA quality after microsurgical repair of varicocele

Abstract: Varicocele is currently the most common irregularity identified in males that is associated with impaired spermatogenesis. It primarily presents in the form of decreased sperm count and motility, abnormal morphology, and significantly increased sperm DNA fragmentation. Several studies have shown that surgical repair improves semen parameters and increases the odds of spontaneous pregnancy. However the exact effect of surgical repair treatment remains controversial. Therefore, the aim of our study was to evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(44 citation statements)
references
References 21 publications
1
43
0
Order By: Relevance
“…As expected and in agreement with background literature [42][43][44], the mean percentage of sperm DNA fragmentation was higher in individuals with varicocele compared to fertile men. In addition, Park et al [45] demonstrated a significant correlation between the expression of PLCζ and the DNA oxidation status assessed using 8-hydroxy-2-deoxyguanosine in human spermatozoa [45].…”
Section: Discussionsupporting
confidence: 92%
“…As expected and in agreement with background literature [42][43][44], the mean percentage of sperm DNA fragmentation was higher in individuals with varicocele compared to fertile men. In addition, Park et al [45] demonstrated a significant correlation between the expression of PLCζ and the DNA oxidation status assessed using 8-hydroxy-2-deoxyguanosine in human spermatozoa [45].…”
Section: Discussionsupporting
confidence: 92%
“…Several studies have indicated that high levels of ROS in seminal fluid increase the risk of male infertility including varicocele (9,10). Elevated levels of ROS in semen samples of varicocele infertile men were observed, which were associated with an increased DNA fragmentation index (9,11,12). These findings suggest that the imbalance between oxidant capacity and the natural antioxidant defense system could play a role in varicocele-associated infertility.…”
Section: Introductionmentioning
confidence: 94%
“…[2][3][4] While varicoceles are the most easily treatable cause of male infertility, these vascular malformations are associated with a progressive worsening of testicular function if left untreated. [5][6][7] Varicocele repair improves semen quality and sperm DNA integrity, 8 increases clinical pregnancy and live birth rates during in-vitro fertilization (IVF) via intra-cytoplasmic sperm injection (ICSI) 9 and potentially recovers semen parameters in men with nonobstructive azoospermia. 10,11 While the effects of varicocele repair are well-established, the method of correction that is most cost-effective, is controversial.…”
Section: Introductionmentioning
confidence: 99%